Comparison of Behavior Problems and School Achievement between Children with and without Motor Problems - Batoul Ahadi (University of Social Welfare and Rehabilitation Sciences, 2009)
Objective: This study investigated behavior problems and educational achievement between children with and without motor problems. Materials & Methods: Seventeen children with motor problems (as case group) and twenty five children without motor problems (as control group) whom had been identified by Lincoln-Oseretsky Motor Development Scale, were randomly selected and participated in this comparative study. The parent form of the Child Behavior Checklist was used to assess children's emotional and behavioral problems. Data were analyzed by Independent T test. Results: Results revealed that children with motor problems obtained significantly poorer scores on school achievement areas than control group (P<0.001). Children with motor problems were also found to evidence relatively high level of total, Internal, external and social problems , somatic complaints, attention deficit and reclusion based on parent reports (P0.05). Conclusion: These findings indicate that all children with movement problems are at risk for problems on behavioral and school achievement areas. Assessment of children with motor problems, regardless of the degree or severity of these problems should examine a wide range of functions in addition to motor functioning.